Cultivation of Family Medicinal Plants using the Verticulture Method as Efforts to Use Narrow Yard Land in Rawamangun, East Jakarta - Adisyahputra; Yulia Irnidayanti; Asharo, Rizal Koen; Lisanti, Elsa; Indrayanti, Reni; Pasaribu, Pinta Omas; Priambodo, Rizky; Rizkawati, Vina (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
The area of RW 01 Rawamangun, Pulogadung District, East Jakarta does not have an allocation of open land, so there is a minimum of green yards. The technology introduced in this community service activity is the cultivation of family medicinal plants in yards using the verticulture method. The purpose of this community service activity is to convey information about the cultivation of family medicinal plants through lectures, discussions, and direct practice of cultivating family medicinal plants in yards using the verticulture method. Evaluation of participants' knowledge improvement was carried out by pre- and post test after counseling and cultivation practices. Skills participants are carried out when evaluating the practice of cultivating medicinal plants in their yards. The results of the activity showed an increase in basic knowledge regarding the types, benefits, and techniques of cultivating family medicinal plants from technology. Family medicinal plant service activity is classified as successful and beneficial, due to increased knowledge more than 60 in average test scoring. The skills evaluation showed that some residents were able to plant and maintain family medicinal plants on a narrow plot of land using the proper verticulture method. The results of the cultivation of these medicinal plants, apart from being one of the real actions of plant greening, can also be in the form of powder products which can then be consumed as a body health measure or sold.